Strengths-based Leadership and Employee Strengths Use: The Roles of Strengths Self-efficacy and Job Insecurity - Wang, Fuxiang; Ding, He (Revista de psicología del trabajo y de las organizaciones, 2023)
Through the lens of self-efficacy and conservation of resources theories, the present study aims to test the mediating role of strengths self-efficacy and the moderating role of job insecurity in the relationship between strengths-based leadership and employee strengths use. Research data from 286 employees working in various organizations in China were gathered at three points in time, spaced by a four-week interval. A moderated mediation path analysis was utilized to test our hypotheses. Results demonstrated that strengths self-efficacy mediates the positive association of strengths-based leadership with employee strengths use, and job insecurity attenuates the direct association of strengths-based leadership with strengths self-efficacy and the indirect relationship of strengths-based leadership with employee strengths use through strengths self-efficacy. The present study advances our understanding of the underlying mechanisms of the relationship between strengths-based leadership and employee strengths use.